Effects of the surface conductivity and the IMF strength on the dynamics of planetary ions in Mercury's magnetosphere. Issue 6 (21st June 2013) - Seki, K.; Terada, N.; Yagi, M.; Delcourt, D.C.; Leblanc, F.; Ogino, T.
Abstract : [1] To examine the effects of planetary surface conductivity and the southward interplanetary magnetic field (IMF) strength on ion dynamics, systematic trajectory tracings of Na + ions were performed in the electric and magnetic field configurations obtained from magnetohydrodynamics (MHD) simulations of the solar wind‐Mercury interaction. Comparison with a previous study, which used an analytical model that rescaled the Earth's magnetosphere and assumed the existence of the distant neutral line (DNL) in Mercury's magnetotail, shows a drastic change in the Na + precipitation pattern due to the formation of the near‐Mercury neutral line (NMNL) in MHD simulations. The Na + precipitation band at approximately 30° of latitude (LAT), which was obtained in the previous study, disappeared in the equivalent low‐conductivity MHD case due to the NMNL formation, while the NMNL formation causes high‐energy Na + precipitation in the equatorial region. The change in strength of the southward IMF (sBz) alters the location of the NMNL and the Na + precipitation pattern. In the low‐conductivity sBz = 5 case, both the equatorial precipitation and the Na + band at approximately LAT = 30 are formed. In the high‐conductivity sBz = 5 case, magnetospheric convection through the polar regions is suppressed, which results in a region of dense Na + near the planet. These results suggest that the precipitation pattern of planetary ions onto Mercury's surface changes significantly with the activity level of Mercury's magnetosphere. It is also suggested that observations of the magnetospheric convection, the distribution of Na + ions around the planet, or the precipitation pattern of Na + ions onto the planetary surface can provide us information about the surface conductivity. Key Points: Na+ precipitation band disappears by formation of the near-Mercury neutral line Na+ precipitation pattern depends on the strength of the southward IMF Warm (cold) dense Na+ at low (high) latitudes under high surface conductivity